JARE-43 ジンコウ ジシン タンサ ニオケル アイスレーダー ニヨル ヒョウショウ アツ ソクテイ - 高田, 真秀; タカダ, マサミツ; 戸田, 茂; トダ, シゲル; 神谷, 大輔; カミヤ, ダイスケ; 松島, 健; マツシマ, タケシ; 宮町, 宏樹; ミヤマチ, ヒロキ; Takada, Masamitsu; Toda, Shigeru; et al. (2003)
P(論文) 第43次日本南極地域観測隊(43次夏隊)は,みずほ高原において地殻構造の解明を目的に,ダイナマイト震源による地震探査を行った.この探査と同時に,探査測線下の基盤地形の詳細な分布を求めるため,アイスレーダーによる測定を実施した.本報告では,アイスレーダー測定の概要と得られた結果について報告する. A seismic exploration was conducted in the austral summer of 2001-2002 by the 43rd Japanese Antarctic Research Expedition (JARE-43) on the Mizuho Plateau, East Antarctica. We carried out the radio echo sounding survey along the seismic line in order to estimate the distribution of bedrock altitude. This report describes the outline of the radio echo sounding survey and the obtained result. departmental bulletin paper